Viscosupplementation with High Molecular Weight Hyaluronic Acid for Hip Osteoarthritis: a Systematic Review and Meta-Analysis of Randomised Control Trials of the Efficacy on Pain, Functional Disability, and the Occurrence of Adverse Events - Patel, R; Orfanos, G; Gibson, W; Banks, T; McConaghie, G; Banerjee, R (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2024)
PURPOSE OF THE STUDY: Hip osteoarthritis (OA) has a prevalence of around 6.4% and is the second most commonly affected joint. This review aims to assess the clinical outcomes of intra-articular high molecular weight hyaluronic acid (HMWHA) in the management of hip osteoarthritis. MATERIAL AND METHODS: We conducted a comprehensive search across PubMed, Google Scholar, and the Cochrane Library for randomised trials investigating the effectiveness of high molecular weight hyaluronic acid (HMWHA) in the treatment of hip osteoarthritis. Quality and risk of bias assessments were performed using the Cochrane RoB2 tool. To synthesise the data, we utilised the Standardised Mean Difference (SMD) for assessing pain relief through the Visual Analogue Scale (VAS) and the Lequesne index (LI) for evaluating functional outcomes. Risk Ratio (RR) was calculated to assess the occurrence of complications. RESULTS: A total of four studies involving HMWHA and control groups were included. The standardised mean difference (SMD) for the Visual Analogue Scale (VAS) (SMD -0.056; 95% CI; -0.351, 0.239; p = 0.709) and the Lequesne index (SMD -0.114; 95% CI; -0.524, 0.296; p = 0.585) were not statistically significant. Analysis for complications demonstrated an overall relative risk ratio (RR) of 0.879 (95% CI; 0.527, 1.466; p = 0.622), and was not statistically significant. DISCUSSION AND CONCLUSIONS: Intra-articular HMWHA in hip OA can significantly reduce pain and improve functional recovery when compared with the condition before treatment. However, there is no significant difference between HMWHA, or saline, or other therapeutic treatments. Currently, available evidence indicates that intra-articular HMWHA in hip OA would not increase the risk of adverse events. KEY WORDS: hip osteoarthritis, hyaluronic acid, intra-articular, molecular weight, viscosupplementation.
Keywords: Molecular Weight; Viscosupplements; molekulová hmotnost; Osteoarthritis, Hip; artróza kyčelních kloubů; výsledek terapie; viskosuplementace; injekce intraartikulární; Pain Measurement; měření bolesti; kyselina hyaluronová; Injections, Intra-Articular; Randomized Controlled Trials as Topic; Humans; Hyaluronic Acid; viskosuplementy; randomizované kontrolované studie jako téma; Treatment Outcome; lidé; Viscosupplementation